(untitled) (KMC Journal, 2023)
The study objective is to evaluate the current drinking water quality in Baglung Bazar. In this investigation, the physio-chemical characteristics of water samples were assessed using tried-and-true techniques. To gauge the degree of bacterial contamination, the total number of coliforms was measured using a conventional membrane filtering method. Random water samples were taken and examined from a number of locations close to Baglung Bazar. The mean water sample’s temperature was 22.3°C. Maximum and minimum temperatures were reported in S6 (24.7°C) and S10, respectively (18.9°C). In filtered water samples, the pH was found to range from 7.29 to 8.1, which is within the acceptable range at the time of the study. The S7, S3, and S8 taps’ electrical conductivity measurements showed minimum and maximum values of 70 S/Cm and 145 S/Cm, respectively. All of the samples were within the 20 to 35 mg/L range for hardness. The iron readings typically recorded ranged from 0.10 to 0.35 mg/L. The S2, S4 and S8 contained the highest concentrations (0.30 mg/L and 0.35 mg/L, respectively). It was found that none of the samples in the current investigation contained Arsenic. Out of 10 sources examined, six (60%) were Coliform-free, while 40 (40%) were determined to be contaminated with total Coliform. The results of the investigation back up the claim that the drinking water in Baglung Bazar is currently unsatisfactory and unsafe for direct consumption. To prevent the spread of waterborne diseases, drinking water must be frequently tested and cleansed before use.